Antidiabetic and antidiarrheal effects of the methanolic extract of Phyllanthus reticulatus leaves in mice - Ripa, Farhana Alam; Khatun, Mst. Hajera; Nesa, Mst. Luthfun; Islam, Rafikul; Al mamum; Kadir, Shahin (© 2014 Elsevier (Singapore) Pte Ltd, 2016)
This article was published in Asian Pacific Journal of Reproduction [© 2014 Elsevier (Singapore) Pte Ltd] and the definite version is available at: http://ac.els-cdn.com/S2305050014600154/1-s2.0-S2305050014600154-main.pdf?_tid=4cb9bd22-afc3-11e6-8aa5-00000aacb361&acdnat=1479716582_9ed93185b04db32d8b3df2c31398dc82 The article website is at: http://www.sciencedirect.com/science/journal/23050500